Avaliação da radioatividade natural na região do manancial da APA Passaúna em Campo Largo/RMC - Martin, Aline Cristina (2019)
Exposure to natural radiation is present in environments and there are regulations that limit relative concentration and dose. Radium is present in rocks, soil, water and minerals and is an important element related to human exposure. Radon is in gaseous form, thus having greater mobility. There is an important relationship between radon exposure and lung cancer, and radon is considered the second cause of this cancer. Gamma radiation dose also contribute to radiation exposure, but there are no specific regulamentation governing exposure limits for natural gamma radiation in Brazil. The objective of this research is to evaluate the natural radioactivity in the region of the APA Passaúna spring in Campo Largo / RMC, by measuring the radium and radon concentration in water and soil of the region and the dose related to the natural gamma radiation present at the soil interface atmosphere in the area. Environmental gamma measurements were made in the region, as well as radon and radium monitoring in water and soil. Due to the 1600-year half-life of radium, the secular equilibrium between this isotope and radon was used to determine radium concentration in water samples. The most significant values of the gamma measurement spectrum were used to focus to the areas of interest in radium and radon monitoring. The results of the environmental gamma spectrometry measurements indicated values that ranged from 0.052 to 0.204 µSv/h, which are below the general population limit of 10 mSv/y, even considering the correlated errors. Radon concentration values in well water samples were 6.16 ± 0.06 and 2.18 ± 0.03 Bq/L, values that are above of the established limit of 0.5 Bq/L, but after reaching the secular equilibrium their values were 0.16 ± 0.02 and 0.23 ± 0.02 Bq/L, both within the limits. Both samples taken from the Passaúna dam and samples from secondary lakes analyzed present radium concentration values within the range, 0.395 ± 0.031 Bq/L; 0.220 ± 0.046 and 0.234 ± 0.020; respectively. The concentration of Rn in the soil ranged from 9,200 ± 800 to 112,000 ± 14,000 Bq/m³. The results evidenciate that there is no clear relationship between the highest dose values and the highest radon and radon concentration values. The research developed serves as a reference in contributing with data on natural radioactivity.